Development and characterization of a new oral dapsone nanoemulsion system: permeability and in silico bioavailability studies - Monteiro LM (Dove Medical Press, 2012)
Lidiane M Monteiro,1 Viviane F Lione,1 Flavia A do Carmo,1 Lilian H do Amaral,1 Julianna H da Silva,2 Luiz E Nasciutti,2 Carlos R Rodrigues,1 Helena C Castro,3 Valeria P de Sousa,1 Lucio M Cabral11Faculdade de Farmácia, Universidade Federal do Rio de Janeiro, 2Instituto de Ciências Biomédicas, Universidade Federal do Rio de Janeiro, 3Instituto de Biologia, Universidade Federal Fluminense, Niterói, Rio de Janeiro, BrasilBackground: Dapsone is described as being active against Mycobacterium leprae, hence its role in the treatment of leprosy and related pathologies. Despite its therapeutic potential, the low solubility of dapsone in water results in low bioavailability and high microbial resistance. Nanoemulsions are pharmaceutical delivery systems derived from micellar solutions with a good capacity for improving absorption. The aim of this work was to develop and compare the permeability of a series of dapsone nanoemulsions in Caco-2 cell culture against that of effective permeability in the human body simulated using GastroplusTM software.Methods and results: The release profiles of the dapsone nanoemulsions using different combinations of surfactants and cosolvent showed a higher dissolution rate in simulated gastric and enteric fluid than did the dispersed dapsone powder. The drug release kinetics were consistent with a Higuchi model.Conclusion: This comparison of dapsone permeability in Caco-2 cells with effective permeability in the human body simulated by Gastroplus showed a good correlation and indicates potential improvement in the biodisponibility of dapsone using this new system.Keywords: dapsone, nanoemulsions, antibacterial, permeability, Caco-2 cell, GastroplusTM